Delayed cord clamping in Nepal - Evidence for implementation. - Rana,Nisha
ABSTRACT: The aims of this thesis were to investigate effects of timing of umbilical cord clamping on newborn health, and on infant outcomes up to 12 months of age in a high-risk population and to explore the context of implementing changed umbilical cord clamping practices in Nepal. A randomised controlled trial with 540 late preterm and term infants born by normal vaginal delivery was set up at a maternity hospital in Kathmandu, Nepal. Infants were enrolled in two parallel groups (1:1 ratio), randomised to early (ECC) (≤60 seconds) or delayed cord clamping (DCC) (≥180 seconds). To get a deeper understanding of barriers and enablers for change in clinical practise in relation to cord clamping, a qualitative study with delivery staff was set up. Focus group discussions and key informant interviews were conducted at two major delivery hospitals in Kathmandu. Paper I showed that DCC was an effective intervention to reduces anaemia at 8 and 12 months of age in a high-risk population, which may have major positive effects on infants' health and development. Paper II utilised the Ages and Stages Questionnaire (ASQ) to assess neurodevelopment in infants at 12 months of age. The result showed DCC was associated with an improvement of the overall neurodevelopment at 12 months of age as compared to infants in the ECC group. Paper III showed that DCC was not associated with an increased risk of hyperbilirubinemia during the first day of life or risk of jaundice within 4 weeks compared with the ECC group. Paper IV demonstrated how a positive attitude towards DCC and a will to rely on research evidence when striving to do good are facilitators of change in clinical practice. However, the participants in the study were hesitant to apply DCC due to lack of national or institutional protocols and formal training. Consequently, they were forced to take informal decisions and rely on alternate sources of information. In conclusion, delaying umbilical cord clamping for 180 seconds is safe and associated with a significantly reduced risk of anaemia at 8 and 12 months which may have neurodevelopmental effects at a later age and is not associated with an increased risk of hyperbilirubinemia during the first days of life or risk of jaundice within 4 weeks of age. In order to change cord clamping practices to comply with evidence and policies health-care staff needs to be better supported by the governance structures of the health system, with clear and approved guidelines made available and coherent training and support. Keywords: Attitude, Clinical Practice, Ferritin, Haemoglobin, Iron deficiency, Iron deficiency anaemia, Iron status, Jaundice, Neonatal hyperbilirubinemia, Newborn, Neurodevelopment, Randomized controlled trial, Umbilical cord clamping.